Spatial dimensions of trade liberalization and economic convergence : Mexico 1985-2002 - Aroca, Patricio, -1960 -1960 (Policy research working paper, 2005)
"This paper studies the spatial dimension of growth in Mexico over the past three decades. The literature on regional economic growth shows a decrease in regional dispersion from 1970 to 1985, and a sharp increase afterward coinciding with the trade liberalization of the Mexican economy. Using spatial econometric, tools the authors analyze how the process of convergence/divergence has mapped spatially and whether it makes sense to talk about spatial regions in Mexico. Although the rich North-poor South dichotomy has dominated this phenomenon, interesting patterns emerge. Namely the distribution of growth after Mexico's post-liberalization seems to be much less associated with distance to the United States than the authors had initially expected. "--World Bank web site